Exploring beneficial effects of phytobiotics in marine shrimp farming: A review - Seong Wei, Lee; Mohamad Sukri, Suniza Anis; Tahiluddin, Albaris B.; Abdul Kari, Zulhisyam; Wee, Wendy; Kabir, Muhammad Anamul (Elsevier BV, 2024)
Marine shrimp farming, mainly Penaeus monodon and Litopenaeus vannamei, is an important component of the aquaculture industry. Marine shrimp farming helps produce a protein source for humans, provides job opportunities, and generates lucrative profits for investors. Intensification farming practices can lead to poor water quality, stress, and malnutrition among the farmed marine shrimp, resulting in disease outbreaks and poor production, impeding the development of marine shrimp farming. Antibiotics are the common short-term solution to treat diseases in marine shrimp farming. Moreover, the negative impacts of using antibiotics on public health and the environment erode consumer confidence in aquaculture products. Recently, research on using phytobiotics as a prophylactic agent in aquaculture has become a hot topic. Various phytobiotics have been explored to reveal their beneficial effects on aquaculture species. In this review paper, the sources and modes of action of phytobiotics are presented. The roles of phytobiotics in improving growth performance, increasing antioxidant capacity, enhancing the immune system, stimulating disease resistance, and mitigating stress due to abiotic factors in marine shrimp culture are recapitulated and discussed.
Keywords: H1-99; Disease resistance; Science (General); Growth performance; Gut microbiota; Review Article; Stress mitigation; Social sciences (General); Q1-390; Immune system; Antioxidant; 2. Zero hunger; 3. Good health; 14. Life underwater